Traumatic Brain Injury and Hypopituitarism - Gianluca Aimaretti; Ezio Ghigo (The Scientific World Journal)
Results of recent and ongoing studies have made it clear that brain injuries like Traumatic Brian Injury (TBI) pose substantial risk to pituitary function, perhaps even greater risk than previously believed. Patients with TBI should be screened both prospectively and retrospectively for isolated, multiple and even total pituitary deficits. It is well known that, patients with “classical” hypopituitarism (due to primary hypothalamic-pituitary pathologies) do benefit from hormonal replacement therapy. It has been suggested that patients with TBI-induced hypopituitarism may benefit with appropriate hormonal replacement receiving replacement therapy such as anti-diuretic hormone (ADH), glucocorticoid and thyroid hormones when needed. Gonadal and recombinant human Growth Hormone (rhGH) replacement therapy should also be introduced if there are deficiencies demonstrated and even reconfirmed in a second step. The signs and symptoms of post-TBI hypopituitarism may be masked by what has been assumed to be merely the post-traumatic syndrome. By increasing awareness among physicians of the risks of brain injuries–induced endocrinopathies and the need for appropriate endocrinological testing, it may be possible to improve the quality of life and enhance the rehabilitation prospects for these patients. In most instances, these patients are first seen and treated by trauma surgeons and neurosurgeons, and subsequently by rehabilitation physicians; they must be knowledgeable about the risks of hypopituitarism so that they can determine which patients are candidates for screening for hypopituitarism. In addition, endocrinologists and internists must be educated about TBI-induced hypopituitarism and encouraged to actively share their expertise with other physicians.